Imagens e Imaginários: do moderno ao pós-moderno - Rahde, Maria Beatriz Furtado (2007)
The contemporary, postmodern visual manifestations we observe in the media, are in continuous transformation, for they are an important part of the myths of both the cultural and the social imaginary. Thus, in this article we try to establish some relationships (differences) between images produced by the cultural imaginary in films, in comics and other visual manifestations, during modernity as well as in the postmodern era.